Heat of Vaporization and Refractive Index Estimation for Hydrocarbons and Petroleum Fractions based on Simple Models - Khurpade, Pratiksha D.; Nandi, Somnath (Journal of Basic & Applied Sciences, 2023)
The present research reports that simple two parameter and three parameter models integrating normal boiling point, specific gravity and molecular weight of hydrocarbons can effectively be used for estimation of different important properties namely heat of vaporization and refractive index. Multivariate regression analysis was employed for model development based on experimental data of pure hydrocarbons reported in literature. Subsequently, it has been demonstrated that this model can be utilized further for prediction of those properties for different petroleum fractions as well. The developed simple generalized two parameter regression-based models can predict heat of vaporization of pure hydrocarbons (C3 – C30) and petroleum fractions with wide boiling point range from 355.5 to 646.8 K with good accuracy (percentage error less than 10% for pure hydrocarbons and lower than 13% for petroleum fractions) in addition, refractive index of petroleum fractions are estimated with percentage error of less than 4.01%. Moreover, comparison results demonstrated that developed models are more accurate and simpler for practical applications in petroleum industry as compared to earlier published correlations for both pure hydrocarbons and petroleum fractions.